The User Acceptance Test (UAT) for Learning Evaluation using CBT (Computer Based Test) for Students - Badriyah, Ratu Dea Mada; Fachriyah, Eva (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2025)
The Implementation of Computer Based Test (CBT) in Learning Evaluation is increasingly being used in universities. To determine the level of student acceptance of the CBT system, a User Acceptance Test (UAT) is required. This study aims to evaluate student acceptance of the CBT system in learning evaluation using a UAT questionnaire. Data was collected from students of the Faculty Islamic Studies and Education Serang Raya University. The questionnaire was delivered in the form of google form. The results of the study show that students generally accept the CBT system well. The dimensions of ease of use and usefulness have the highest average values, followed by the dimensions of reliability and security. The feedback dimension shows that students have some suggestions for improving the CBT system. These findings indicate that the CBT system has the potential to be an effective tool in learning evaluation, but further improvement and development is needed to increase user satisfaction.